FM2-7 Paediatric robot-assisted DBS surgery: electrode problems and revision techniques. Issue 3 (14th February 2019) - Oviedova, A; Ellenbogen, J; Hasegawa, H; Kaminska, M; Perides, S; Lumsden, D; Lin, J; Ashkan, K; Selway, R
Abstract : Objectives: We review our cases of hardware problems requiring revision surgery and consider the technical aspects of revising the electrodes, including a frameless technique using the Renishaw Guide tubes. Design: Retrospective Review. Subjects: Children (≤18 years old) who presented with hardware problems following implantation of a DBS for dystonia at King's College Hospital between May 2005 and April 2018. Methods: Information was obtained from a prospectively kept database. Results: Of 166 paediatric patients with DBS, 25 patients had hardware problems, and of these 21 (13%) patients had specifically electrode problems requiring replacement/revision of one or more electrodes. 7 patients had high impedances requiring revision, without obvious lead migration of fracture. 7 patients had lead migration and a further 7 patients had a lead fracture with or without lead migration. 15 patients had original DBS insertion with the Leksell Stereotactic System utilising the Medtronic Stimlock for lead fixation. 6 patients had DBS inserted with the Renishaw Sterotactic Robot and utilised the Renishaw Guide Tubes, in these patients who required lead replacement it was possible to revise the electrode without using stereotactic apparatus. As the guide tubes are implanted in the correct trajectory it is possible to measure the distance required to advance/implant the lead within this to target without the need for full stereotactic reimplantation. Conclusions: Electrode dysfunction is relatively common in children with DBS and a systematic approach is required to identify the cause. When an electrode requires repositioning or replacement, the procedure can be performed in the conventional manner with a stereotactic frame, or freehand without a frame if a Renishaw Guide tube is used at time of first insertion.